2020
DOI: 10.1080/0965254x.2020.1749875
|View full text |Cite
|
Sign up to set email alerts
|

Exploring values affecting e-Learning adoption from the user-generated-content: A consumption-value-theory perspective

Abstract: The aim of this study is to utilise the user-generated content from social-media platforms and merchandise websites to explore various values affecting behavioural intention in context of e-Learning services from the consumptionvalue-theory perspective. This study has utilised a novel mixed-method approach based on natural language processing (NLP)-techniques for the both the qualitative and quantitative analysis. This study has used user-generated content of Coursera (an e-Learning service) consisting of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…Saga et al [ 69 ] proposed a hybrid framework integrating the LDA and proposed a process of analyzing SEM using LDA. Ray et al [ 70 ] also adopted the LDA and the SEM to explore various values affecting behavioral intention in the context of e-learning services. Both studies used the words as observation variables and the topics as the latent variables for SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Saga et al [ 69 ] proposed a hybrid framework integrating the LDA and proposed a process of analyzing SEM using LDA. Ray et al [ 70 ] also adopted the LDA and the SEM to explore various values affecting behavioral intention in the context of e-learning services. Both studies used the words as observation variables and the topics as the latent variables for SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have been studying barriers in various contexts like, healthcare (Brown, 2005), adoption of renewable energy innovations (Reddy and Painuly, 2004), etc. For any service provider it is vital to know the barriers that customer's face because the advancement of technological innovations has not only changed the lifestyle of people (Ray et al, 2020b) but has also led to increase in competition in almost every sector (Ray et al, 2019a). The easy accessibility of various internetbased services has also increased barriers faced by consumers.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The qualitative-based interviews have revealed that facilitator teaching and communication skills affect a person's motives to pursue a particular course. Researchers (Ray et al, 2020b) noted a positive influence on facilitator quality on intention to take up online courses. Researchers have also noted that teaching quality affects not only students' learning (Sandnes and Jian, 2001) but also their satisfaction (Jian and Sandnes, 2009).…”
Section: Value Barriermentioning
confidence: 99%
“…The Consumption Value Theory (CVT) is used to capture the different value-oriented elements that affect the behavior choice of customers. Understanding the issue of how customer perceptions and factors that influence the customers' satisfaction and the adoption of various innovation represent a significant market research task (Ray et al, 2020). CVT was originally developed by Sheth et al (1991) understand the customers' choices of whether to buy or nor buy in the marketing field (Biswas and Roy, 2015).…”
Section: The Consumption Value Theorymentioning
confidence: 99%
“…Functional value generally is more associated with the functional aspects of the service platforms (e.g. website, application) (Ray et al, 2020). There are studies regarding that the functional value influences mobile services (Turel et al, 2007), use of mobile application (Zolkepli et al, 2020, Spink et al, 2011, information systems (Tzeng, 2011).…”
Section: Figure 2 Conceptual Research Modelmentioning
confidence: 99%